SOCIAL SOFTWARE TOOLS AND KNOWLEDGE SHARING AMONGTHE STUDENTS: MALAYSIAN UNIVERSITIES PERSPECTIVES - KAEOMANEE, YOSSAWADEE (2013)
Knowledge sharing among students has become an essential activity which can result in the improvement of students' learning outcome. However, the current e-learning technology, such as the learning management system, applied in the Malaysian higher education institutions lacks the characteristics which could support this activity.